K-POP AS A TOOL OF REPUBLIC OF KOREAâ€™S PUBLIC DIPLOMACY - A Novita Annisa Aslam (HI 16 UMY 199, 2016)
*199 spread throughout the world, starting from East Asia to South East Asia and even Europe and America. Korean wave has considerably numerous followers all around the world, according to some studies by scholars. Korean wave or Hallyu varies from television drama, movies, music and dance (kpop), food (hanshik), language (Hangeul), fashion, and even cosmetic products. Hallyu has become a valuable soft power asset of South Korea. The term â€œHallyuâ€ derived from mandarin word, â€œHanliuâ€, which literally means Korean Wave. This term suddenly arised because in 1997, the korean drama, What is Love About was broadcasted in China in CCTV channel and the rating of the drama was the second highest in the history of China entertainment industry. Based on this, the chinese journalists started to refer to Korean wave as Hallyu This paper will discuss about K-pop as one of the tools of Republic of Koreaâ€™s public diplomacy. As stated in the Koreaâ€™s Diplomatic White Paper 2012, 2013 and 2014, that hallyu, including K-pop, is an important part of Koreaâ€™s public diplomacy. Korean Wave has expanded with the popularity of Korean films and the worldwide spread of K-Pop music. Based on its global popularity, K-pop has proven to be positively welcome in many countries around the world. Aware of the fact that k-pop has become a global phenomenon, the government of Korea has made a good use of it in order to promote Korea to the foreigners. It is one of the most important tools of Koreaâ€™s public diplomacy. Keywords: Republic of Korea; Public Diplomacy; Korean Wave; Hallyu; K-pop.